Arterial aging and the autonomic nervous system: is the relationship differently modified by physical activity in men and women? - Sestu, Alessandro; Lai, Alessandro; Murru, Veronica; Favale, Agnese; Scuteri, Angelo (Frontiers in Aging, 2025)
IntroductionArterial aging is an independent risk factor for cardiovascular morbidity and mortality and is beneficially influenced by physical activity. However, it remains unclear whether the impact of physical activity on arterial stiffness differs between men and women and whether selected factors contribute to sex differences in the association of physical activity with arterial aging.MethodsData from healthy volunteers (n = 265; mean age: 40 ± 16 years, 42.6% women) were used. Arterial aging was assessed using carotid-to-femoral pulse wave velocity (PWV). Volunteers were categorized as sedentary (no regular weekly physical activity) and regularly active.ResultsPhysically active men presented a significantly lower PWV than the sex-matched sedentary group (8.2 ± 0.2 versus 9.0 ± 0.3 m/s, p < 0.01). In the fully adjusted model (adjusted for age, blood pressure, heart rate, muscular mass, fat mass, and visceral adiposity), a steeper association between PWV and autonomic nervous system activity was observed in sedentary individuals than in physically active men. Physical activity was associated with no difference in PWV (7.9 ± 0.3 versus 7.9 ± 0.2 m/s), and no significant association between PWV and autonomic nervous system activity was observed in women.ConclusionPhysical activity was associated with a lower increase in arterial aging, indexed as pulse wave velocity, for any increase in autonomic nervous system activity in men. This effect was independent of age, blood pressure, and adiposity. The same effect was not observed in women. Future studies should clarify how these findings may inform a personalized approach to cardiovascular (CV) risk reduction.